Case Study : Afiat Oil Company Sdn Bhd / Aiman Zikri Zahari - Zahari, Aiman Zikri (2021)
This case study was about Afiat Oil Company. The purpose of this case study is to study more about entrepreneurship. The case study was conducted by me as an individual project, Mirza Aiman bin Mohd Hadi. One of the components in this report is introduction. Then, in the introduction, the researches is about what is the entrepreneurship education and entrepreneur. The next component is business description which are included the background of the company, name of company and when they start, products and financial achievement. Another component is entrepreneurial characteristic, its about what the owner do to success. After that, analysis during the case study included also the strength, weakness, opportunity and threat for the company. Next is appendices of the product and place of the company. I hope this company will do better in their business and can become more successful.